Pigeon tick bite: A neglected cause of idiopathic nocturnal anaphylaxis. Issue 4 (22nd November 2017) - Rolla, G.; Heffler, E.; Boita, M.; Doyen, V.; Mairesse, M.; Cvackova, M.; Debarbieux, S.; Kleine‐Tebbe, J.; Ollert, M.; Raulf, M.; Bircher, A. J.; Hilger, C.
Abstract: Anaphylaxis is a serious systemic allergic reaction with rapid onset and potentially life‐threatening. We report in detail a case of severe nocturnal anaphylaxis due to pigeon tick bite showing the diagnostic value of the extract and the recombinant allergen in the diagnostic procedures (basophil activation test, IgE immunoblot, and experimental ImmunoCAP). Apart from the presented case, we describe that during the last 10 years, we have collected 28 cases of allergy to Argas reflexus from several European countries. We suspect that this allergy is underdiagnosed because of the lack of diagnostic reagents. Because of the growing number of pigeons in Middle and Southern Europe cities, some cases of idiopathic anaphylaxis could potentially be caused by A. reflexus in those countries. The identification of pigeon ticks as a trigger of anaphylaxis would greatly improve medical care and advice for these patients as the parasite can be exterminated by eradication measures to avoid further incidents.